Detection of Antibiotic Residues in Chicken Eggs from Traditional Markets at Maros Regency Using Bioassay Method - NUR, ADYATMA MUHAMMAD; Suharto, Rian Hari; Mursalim, Muhammad Fadhlullah; Toputri, Nur Aqifah Ahmad (Hasanuddin University, 2025)
Chicken eggs stand as a cornerstone of food security and a vital source of affordable, high-quality animal protein for much of the Indonesian population. However, the food safety integrity of this strategic commodity is currently facing severe challenges due to the threat of antibiotic residues, which have been identified as a primary driver of the global crisis of Antimicrobial Resistance (AMR). The root of this issue often stems from suboptimal health management practices at the farm level, specifically the widespread negligence regarding the mandatory withdrawal period before harvest. This oversight results in the retention and accumulation of veterinary drug residues in animal products intended for human consumption. The presence of antibiotic residues in the food chain is not merely a technical livestock issue but a critical public health threat. Long-term exposure to low-dose residues can trigger bacterial resistance in the human body, leading to reduced efficacy of medical treatments (therapeutic failure) during infections. Furthermore, these residues pose potential risks of hypersensitivity reactions and toxicological effects on consumers. Addressing this urgency, this study was meticulously designed to identify the presence and calculate the prevalence of residues from four major antibiotic classes: Penicillin (PEN), Macrolide (MCR), Aminoglycoside (AMG), and Tetracycline (TCY). The research focused on commercial layer eggs circulated in traditional markets within Maros Regency, South Sulawesi, to analyze residue distribution patterns based on sampling locations. This study employed a cross-sectional design, collecting a total of 50 egg samples from four strategic districts: Turikale, Marusu, Lau, and Bantimurung. To ensure data validity, residue analysis was conducted at the Veterinary Public Health Laboratory of the Maros Veterinary Center (Balai Besar Veteriner Maros). The method utilized was a bioassay screening test strictly adhering to the Indonesian National Standard (SNI) 7424:2008. The laboratory investigation revealed critical findings: the overall prevalence of antibiotic residues was 12%, with 6 out of 50 samples confirmed positive. Specific results indicated that all positive samples were contaminated solely by Penicillin group residues. Meanwhile, residues from the Macrolide, Aminoglycoside, and Tetracycline groups were not detected in any of the tested samples. These findings highlight a specific dependency on beta-lactam antibiotics in the region and underscore the critical need for stricter monitoring and farmer education regarding responsible antibiotic usage to ensure consumer safety. Keywords: antibiotic residues, egg, bioassay